2014
DOI: 10.1080/09593330.2014.951076
|View full text |Cite
|
Sign up to set email alerts
|

Ceramic ware waste as coarse aggregate for structural concrete production

Abstract: The manufacture of any kind of product inevitably entails the production of waste. The quantity of waste generated by the ceramic industry, a very important sector in Spain, is between 5% and 8% of the final output and it is therefore necessary to find an effective waste recovery method. The aim of the study reported in the present article was to seek a sustainable means of managing waste from the ceramic industry through the incorporation of this type of waste in the total replacement of conventional aggregat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 21 publications
1
13
0
3
Order By: Relevance
“…Numerous researchers have identified ceramics as having the potential to replace natural aggregates [5,6]. Some investigations have suggested that ceramic wastes are good materials which could substitute conventional aggregates in concrete [7][8][9]. The influence of ceramic tiles wastes on the structural properties of concrete made using laterite was recently investigated [10].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous researchers have identified ceramics as having the potential to replace natural aggregates [5,6]. Some investigations have suggested that ceramic wastes are good materials which could substitute conventional aggregates in concrete [7][8][9]. The influence of ceramic tiles wastes on the structural properties of concrete made using laterite was recently investigated [10].…”
Section: Introductionmentioning
confidence: 99%
“…Tests of concrete containing ceramic whiteware aggregate have confirmed that the concrete is characterised by a relatively high strength and resistance to an aggressive environment, and has several other advantageous properties discussed below. This was in turn confirmed by the studies [17][18][19] in which only recycled aggregate of ceramic whiteware was used. A positive impact of the use of recycled ceramic aggregates (RCA) consisting of ceramic whiteware was also confirmed in the tests of [20], in which 20 and 25% of coarse NA were replaced with recycled aggregate consisting of crushed ceramic whiteware.…”
Section: Introductionmentioning
confidence: 58%
“…Red ceramics in the form of bricks, breeze-blocks or roof tiles, as well as white ceramics (tableware, sanitary ceramics, electrical isolators), are non biodegradable materials, and their disposal is highly problematic. Studies conducted by [5,6] show that concrete based entirely on white ceramic aggregate does not have different physical and mechanical properties from concrete made of natural aggregate. In the research conducted by [7,9], the material properties of clay cement and ceramic aggregate based concrete were compared to those of concrete made with natural aggregate.…”
Section: Prefacementioning
confidence: 99%